Evaluation of Human Health Risks Associated with Selected Heavy Metal Exposure from Fumarolic Condensates in Mt. Suswa, Kenya - Yator Gideon (Kabarak University, 2025)
Abstract Fumarolic condensates in volcanic terrains often serve as critical water sources for nearby communities but may contain toxic heavy metals mobilized through magmatic degassing and hydrothermal leaching. This study evaluated the potential human health risks associated with exposure to selected heavy metals (arsenic (As), cadmium (Cd), lead (Pb), and mercury (Hg)) in fumarolic condensates from Mt. Suswa, Kenya. Condensate samples were collected from ten modified fumarolic vents actively used by local residents and analyzed using an Agilent 5110 ICP-OES for trace-metal quantification. The mean concentrations of As (3.86 ppb), Pb (1.43 ppb), and Cd (0.85 ppb) were all below World Health Organization (2022) and NEMA (2024) limits, while Hg remained undetected in all samples. The Heavy Metal Pollution Index (HPI) and Heavy Metal Evaluation Index (HEI) indicated moderate contamination (mean HPI = 20.46 ± 12.75; HEI = 0.70 ± 0.28), with higher enrichment observed in inner-caldera fumaroles, reflecting stronger magmatic influence. Health-risk assessment following USEPA (2011) methodology showed that non-carcinogenic hazard quotients (HQ) for As and Cd were below unity for both adults and children, though relatively higher in children, indicating greater susceptibility to chronic exposure. The carcinogenic risk (CR) for As ranged from 9.98 × 10⁻⁵ (F2) to 1.00 × 10⁻⁴ (F4) for adults and 9.78 × 10⁻⁵ (F10) to 1.92 × 10⁻⁵ (F6) for children, with the former slightly exceeding the upper USEPA threshold (10⁻⁶–10⁻⁴), suggesting a low but notable lifetime cancer probability from prolonged exposure. Although overall contamination levels were low, localized enrichment and cumulative exposure may pose health risks to vulnerable populations. These findings underscore the importance of continuous monitoring, community education, and sustainable mitigation strategies such as alternative safe-water supplies and affordable point-of use treatment technologies in geothermal-affected regions.
Full text
Keywords: Mt. Suswa; fumarolic condensates; heavy metals; human health risk